2009
DOI: 10.1111/j.1468-2982.2008.01693.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Impact of Headache in Children: A Critical Review of the Literature

Abstract: Headache is the most frequent neurological symptom and commonest manifestation of pain in childhood. Measuring the impact of headache in terms of health status, functioning and quality of life can inform the prioritization of competing resource claims, screen for unmet need, improve communication between patient and physician and monitor response to treatment. We undertook a critical review of the literature measuring the impact of headache in children and identified 33 papers that contained relevant informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 59 publications
5
77
0
1
Order By: Relevance
“…Headaches are common in all age groups. 12,28,56 Since pineal cysts are also common, a substantial number of patients will present for medical attention with headaches and a pineal cyst that is coincidentally rather than causally associated. In a surgical series of 11 patients with pineal cysts, Fetell et al 19 found that patients with headaches can be expected to have postoperative symptomatic relief only if the headaches were caused by hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…Headaches are common in all age groups. 12,28,56 Since pineal cysts are also common, a substantial number of patients will present for medical attention with headaches and a pineal cyst that is coincidentally rather than causally associated. In a surgical series of 11 patients with pineal cysts, Fetell et al 19 found that patients with headaches can be expected to have postoperative symptomatic relief only if the headaches were caused by hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…These included poorly validated impact measures, absence of power calculations for adequate sampling, and inadequate description of study design and data analysis. 15 There was no population description of headache impact on generic quality of life that allowed comparison to be made with other diseases.…”
Section: Introductionmentioning
confidence: 99%
“…2 For patients, this finding means troublesome symptoms and often a considerable degree of disability with time lost from school, friends, and other activities. 2,3 From a societal perspective, migraine leads to substantial indirect costs from lost productivity and direct costs for health care. 4 Despite migraine's high prevalence and morbidity, relatively few prophylactic drugs have been proven effective among children and adolescents, and they are all associated with a risk of adverse effects.…”
mentioning
confidence: 99%
“…The objectives were as follows: (1) to assess the efficacy of biofeedback on primary attack frequency in children and adolescents with migraine; (2) to assess the efficacy on secondary end points (eg, attack duration, headache intensity, quality of life, disability, acute medication use); (3) to investigate any potential adverse events associated with the treatment; and (4) to conduct a risk of bias assessment of the included studies.…”
mentioning
confidence: 99%